DEFORMATION SHRINKAGE AND CREEP OF CONCRETE IN NATURAL CONDITIONS OF DRY HOT CLIMATE (Spectrum Journal of Innovation, Reforms and Development, 2022)
This article presents the experimental value of the coefficient of thermal expansion of concrete, shrinkage deformations and creep deformations of concrete in dry and hot climates.